FASILITAS DISKONTO (DISCOUNT WINDOWS) SEBAGAI INSTRUMEN MONETER DITINJAU DALAM PERSPEKTIF EKONOMI ISLAM - RINA EL MAZA; EGI PUTRA SETIAWAN (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2019)
The government has an important role in the welfare of the people's economy. One of them is through the role of the central bank by carrying out monetary policy. This policy was adopted by the central bank or Bank Indonesia (BI) through several instruments, including through regulating discount rates for commercial banks. In this case, BI sets the inﬂation target as a reference for determining interest rates. When the inﬂation rate exceeds the targeted, BI will raise interest rates which in turn will reduce the credit issued by commercial banks to the public, because commercial banks must pay higher interest rates to the central bank. And the results of the analysis that the interest rate charged in the credit (Lending Facility) discount facility is classiﬁed as an act of usury. Meanwhile, the proﬁts obtained from the deposit of funds in the Facility Deposit transaction are not permitted in the Islamic economy, because in the Islamic economy there is no interest rate but proﬁt sharing, given the ﬁxed and concrete interest rates. In addition, the discount facility is also incompatible with some Islamic economic principles, including; the principle of Illahiyah, Justice, and the government.